Organic LEDs Based on Bis(8-hydroxyquinoline) Zinc Derivatives with a Styryl Group - Malgorzata Sypniewska; Monika Pokladko-Kowar; Ewa Gondek; Aleksandra Apostoluk; Piotr Kamedulski; Vitaliy Smokal; Peng Song; Junyan Liu; Robert Szczesny; Beata Derkowska-Zielinska (Molecules, 2023)
For the first time, organic light-emitting diodes (OLEDs) based on bis(8-hydroxyquinoline) zinc with a styryl group (ZnStq) dispersed in poly(N-vinylcarbazole) matrix (ZnStq_R:PVK, where R = H, Cl, OCH3) were fabricated. The ZnStq_R:PVK films made via the spin-coating method were used as the active layer in these devices. The produced OLEDs showed strong electroluminescence with yellow emissions at 590, 587 and 578 nm for the ZnStq_H:PVK, ZnStq_Cl:PVK and ZnStq_OCH3:PVK, respectively. For all the studied thin films, the main photoluminescence emission bands were observed between 565 and 571 nm. The OLED with the ZnStq_OCH3:PVK layer with a narrow electroluminescence spectrum was found to have sufficient color purity to produce ultra-high-resolution displays with reduced power consumption (full width at half maximum of 59 nm, maximum brightness of 2244 cd/m2 and maximum current efficiency of 1.24 cd/A, with a turn-on voltage of 6.94 V and a threshold voltage of 7.35 V). To characterize the photophysical properties of the active layer, the ZnStq_R:PVK layers samples were additionally deposited on glass and silicon substrates. We found that the obtained results predestine ZnStq_R:PVK layers for use in the lighting industry in the future.